?It Gave Me Hope? Experiences of Diverse Safety Net Patients in a Group Acupuncture Intervention for Painful Diabetic Neuropathy (Mary Ann Liebert, 2020)
Purpose: To explore the experiences of living with painful diabetic neuropathy (PDN) and with a group acupuncture intervention in a sample of low-income, diverse patients. Methods: We conducted a randomized clinical trial of a 12-week group acupuncture intervention for PDN. Data included validated measures of patient-reported outcomes, including pain and quality of life (QOL), as well as semistructured qualitative interviews about participants' experiences with PDN and the intervention. Interview transcripts were coded and analyzed using an inductive thematic framework. Results: We recruited 40 participants from diverse racial/ethnic backgrounds from a public hospital and conducted in-depth qualitative interviews with a subset of 17 participants. Participants randomized to acupuncture experienced greater decreases in pain compared with usual care as well as improved QOL. In interviews, they described a myriad of socioeconomic and personal life stressors that compounded the significant suffering and disability brought on by PDN. Those who received acupuncture were able to decrease reliance on pain medication, improve their sleep and daily function, reduce stress, and engage more with their own self-care. They noted that the acupuncture intervention also gave them hope in the face of their chronic disease. Conclusion: Acupuncture is a valuable adjunct treatment for low-income and marginalized populations with PDN. In addition to reducing pain and improving QOL, acupuncture may offer powerful benefits by increasing patient activation and hope.